Repercussions of the regional strategic balance on the international powers in the Middle East - Al-Qaisi, Lecture. Dr Tuka ayad Khalil Ibrahim (The International and Political Journal, 2023)
The strategic balance in the Middle East is one of the most important topics that have captured the attention of researchers and thinkers. That was due to the potential and capabilities that this region possesses and could have a significant impact on international strategic interests and thus on international and regional balances. The Middle East region witnessed many equilibrium formulas, each of which was an expression of the circumstances and variables that prevailed in the region. Hence the importance of studying the regional and international powers in the Middle East and the most important pressures facing those powers, especially the great powers represented by the United States, the Russian Federation, and China, and their attempts to achieve a strategic balance in the region. The research sought to deal with the following problem: What did the strategic balance look like in the Middle East after 2003, and what regional and international powers were able to impose their will on the region? The research was divided into three chapters, in addition to an introduction, conclusion, and conclusions reached by the researcher. The first chapter was devoted to the theoretical framework of the concept of the Middle East and the strategic balance, while the second one was devoted to studying regional balances and their reflection on the gains of international balances of power. The focus was on the regional powers that are major players in the region, represented by Iran, Turkey, Saudi Arabia, and Israel. Finally, the third chapter dealt with the repercussions of regional balances on international competition in the Middle East.